KONSEP DESAIN APLIKASI SISTEM MANAJEMEN KEPEGAWAIAN BERBASIS WEB PADA PT. BINTANG KOMUNIKASI UTAMA (Application design concept of web-based staffing management system at PT Bintang Komunikasi Utama) - Anggeri S. Nurjaman; Verdi Yasin (Journal of Information System, Informatics and Computing, 2020)
The spirit of work can be measured through the presence of employees in the workplace, their responsibility to work, discipline of work in the organization and the level of work productivity. Measuring the low morale of employees includes attendance level, discipline, cooperation and responsibility. Attendance is the presence of employees related to their duties and obligations. In general, agencies or agencies always pay attention to their employees to come so that work is not delayed. To obtain optimal performance from employees, organizations need to create and establish strategies that are oriented towards the same goal. In conventional model employee recruitment tools, requires a lot of things from personnel and honesty employees. This can occur in the manipulation of employee attendance data. With a fingerprint-based system, the process of retrieving employee attendance data reaches 100% accurate because the data is based on the fingerprints of direct employees. Errors and manipulations can be avoided because the reporting becomes automated with the help of the system. The purpose of this staffing management system model as a surveillance media and supporting media decision making for employee performance assessment. It is expected to provide solutions for companies in Employee Performance Assessment who are able to create reports quickly, accurately and in real time.